The Reporting On The 1Malaysia Development Berhad (1MDB) Crisis And Implication On Efficacy Of Economic And Financial News Reporting In Malaysia - Nazmi, Shahrul; Rahim, Mohd Helmi Abd (Advances in Social Sciences Research Journal, 2016)
The accusations made in regard of wrongdoings related to the Malaysian government- linked investment company, 1Malaysia Development Berhad (1MDB) have raised concern on efficacy of economic and financial journalism in Malaysia. The local news agencies’ reporting and the level of knowledge of journalists regarding economic and finance, as regard to the 1MDB issue, is said to be not convincing and has no clear direction, as against the foreign news agencies like Bloomberg, CNBC, or Financial Times. This research aims at trying to understand the views of Malaysian journalists; as to their own level of knowledge, the news content, and of their social and organizational responsibilities. This research attempts to identify, from where or the sources, reporters get their stories, their idea approach to the stories, and, how the news are written. The research also deals on how the economic and financial journalists responded to issues of crisis, their editorial news planning, decision making strategies among them, and what actions are taken in gathering information for this kind of controversial issue. In-depth interviews have been conducted to the economic and financial journalists from several prominent news agencies in Malaysia. The findings indicate that the journalists put priority on journalism ethics that specify journalism’s role to the development of the nation, and, the lack of decision making when dealing with corporate matters and influence. The legal control and ownership of the media organization by the government or the ruling party also determine the pattern of economic and financial news in this country.